2019
DOI: 10.3389/feart.2019.00226
|View full text |Cite
|
Sign up to set email alerts
|

Global Mapping of Citizen Science Projects for Disaster Risk Reduction

Abstract: Citizen science for disaster risk reduction (DRR) holds huge promise and has demonstrated success in advancing scientific knowledge, providing early warning of hazards, and contributed to the assessment and management of impacts. While many existing studies focus on the performance of specific citizen science examples, this paper goes beyond this approach to present a systematic global mapping of citizen science used for DRR in order to draw out broader insights across diverse methods, initiatives, hazards and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 114 publications
0
38
0
1
Order By: Relevance
“…Completeness, filling all the identified data gaps for SDG monitoring (UN Environment 2019) and Timeliness providing early warning of hazards, and reducing the disaster risk (Hicks et al 2019), with the consequent improvement of several SDGs (Kelman 2017).…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%
“…Completeness, filling all the identified data gaps for SDG monitoring (UN Environment 2019) and Timeliness providing early warning of hazards, and reducing the disaster risk (Hicks et al 2019), with the consequent improvement of several SDGs (Kelman 2017).…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%
“…The extensive participation of citizens during the occurrence of disasters not only provides support to relieve the gap of disaster damage and solve vulnerability but also has a positive influence on rebuilding after disasters as well as developing the local community [1][2][3][4][5]. Hicks et al demonstrated that citizens' participation led to global mapping and resulted in enhancing the disaster reduction [6]. They showed how a real-time natural disaster In fact, when disaster strikes, because citizens are present at the scene of a disaster, they can be the "true" first responders, who can actively address community needs by participating in activities such as the restoration of public services and infrastructure [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…From the start, the DIVA model has explicitly represented the costs and benefits of future DRR measures, since it was developed to assist climate adaptation studies. DIVA has been used in several studies at a global scale, including those of Hinkel and Klein (2009) and Hinkel et al (2010Hinkel et al ( , 2014, to assess risks under scenarios of sea level rise, subsidence, and population growth, with several assumptions on future DRR measures. It has also been used by Hallegatte et al (2013) to assess coastal flood risk and the costs and benefits of structural DRR measures in major coastal cities by 2050.…”
Section: Coastal Floodsmentioning
confidence: 99%